2009
DOI: 10.1007/s00018-009-9053-2
|View full text |Cite
|
Sign up to set email alerts
|

Calcium imaging of muscle cells treated with snake myotoxins reveals toxin synergism and presence of acceptors

Abstract: Snake myotoxins have a great impact on human health worldwide. Most of them adopt a phospholipase A2 fold and occur in two forms which often co-exist in the same venom: the Asp49 toxins hydrolyse phospholipids, whilst Lys49 toxins are enzymatically inactive. To gain insights into their mechanism of action, muscle cells were exposed to Bothrops myotoxins, and cytosolic Ca(2+) and cytotoxicity were measured. In both myoblasts and myotubes, the myotoxins induced a rapid and transient rise in cytosolic [Ca(2+)], d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
54
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 44 publications
10
54
1
Order By: Relevance
“…This latter increase could originate from the myotoxin diffusing out from the site of injection and from ATP released by the myotubes directly hit by the myotoxin, or from both effects. Myoblasts close to the injection site remained blue, in agreement with previous findings that they are Mt-II insensitive (15,16); however, their cytosolic Ca 2+ did increase at later times ( Fig. 2 A and D, traces a-c).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This latter increase could originate from the myotoxin diffusing out from the site of injection and from ATP released by the myotubes directly hit by the myotoxin, or from both effects. Myoblasts close to the injection site remained blue, in agreement with previous findings that they are Mt-II insensitive (15,16); however, their cytosolic Ca 2+ did increase at later times ( Fig. 2 A and D, traces a-c).…”
Section: Resultssupporting
confidence: 91%
“…We showed previously that the snake myotoxins, including the Mt-II myotoxin, caused cell death of myotubes in cultured C2C12 cells (15), and this was evident also in the present study, as shown in These results unravel a previously uncharacterized aspect of great significance in the action of B. asper Lys-49 Mt-II myotoxins, as the results show that this myotoxin may damage muscle cells at a distance from the injection site via an indirect action mediated by the ATP released from cells directly hit by the venom, i.e., those close to the tip of the snake fangs. This event can rapidly expand the anatomical dimensions of the direct myotoxin effect and, consequently, the ability of the snake to capture prey.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…3D), showing a parallelism between neurotoxic and myotoxic effects of the myotoxin. Cintra-Francischinelli et al (2009) excluded the possibility that the inactive Lys49 toxins act by binding to a membrane channel, thus increasing its permeability to Ca2+. The authors have shown that the action of myotoxins from snake venoms on muscle cells begins with the activation of membrane acceptors coupled to intracellular Ca 2+ stores, which is rapidly followed by the toxin dependent alteration of membrane permeability to ions (and other molecules).…”
Section: Pharmacologymentioning
confidence: 99%